Occupational preference and realization of difficulties by displaced tribal farm women in hill districts of Assam - Saharia, K K; Johari, M; Talukdar, J (Indian Journal of Animal Production and Management, 2018)
A study on occupational preference and realization of difficulties by the displaced tribal farm women in hilldistricts of Assam in rearing livestock was carried out with stratified randomly selected one hundred eachrespondents from two districts namely Dima Hasao and Karbi Anglong making the total sample size 200.A pre-tested, reliable and valid interview schedule encompassing preference for occupation and a checklist containing seventeen items were used for data collection. Among the displaced tribal farm women,preference of occupation from higher to lower as primary source of livelihood was agriculture, followedby animal husbandry, business, weaving and craft making where service did not feature. The realizationof difficulties by the respondents was in low level and there was no significant mean difference betweenthe two districts. No time for weaving and craft making, needing to put more labour, lack of open grazingfield for livestock, education of children suffering and no recreation against tedious labour were the majorproblems the displaced tribal farm women faced due to rearing of livestock. The realization of difficultieswas positively and high significantly (P